2019
DOI: 10.3382/ps/pez420
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary threonine supplementation on productivity and expression of genes related to protein deposition and amino acid transportation in breeder hens of yellow-feathered chicken and their offspring

Abstract: This study investigated the effects of the dietary threonine (Thr) levels on the performance, offspring traits, embryo amino acid transportation, and protein deposition in breeder hens of yellow-feathered chickens. In total, 720 breeder hens of Lingnan yellow-feathered chickens were randomly assigned to 1 of 6 dietary treatments, with 6 replicates per treatment (20 birds per replicate). The breeder hens were fed either basal diet (Thr = 0.38%) or basal diet supplemented with 0.12, 0.24, 0.36, 0.48, or 0.60% Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 65 publications
(94 reference statements)
1
11
0
Order By: Relevance
“…On the other hand, shell strength and yolk color were affected linearly as AA increased in rearing diets and shell weight and elasticity in a quadratic way. Jiang et al (2019) reported a linear decrease in the eggshell percentage, thickness, and strength in broiler breeders supplemented with Thr ranging from 0.50 up to 0.98% of total dietary content in the laying phase from 28 to 38 wk of age. However, these levels were higher than those used in the experimental rearing diets and standard layer diets in our experiment.…”
Section: Discussionmentioning
confidence: 98%
“…On the other hand, shell strength and yolk color were affected linearly as AA increased in rearing diets and shell weight and elasticity in a quadratic way. Jiang et al (2019) reported a linear decrease in the eggshell percentage, thickness, and strength in broiler breeders supplemented with Thr ranging from 0.50 up to 0.98% of total dietary content in the laying phase from 28 to 38 wk of age. However, these levels were higher than those used in the experimental rearing diets and standard layer diets in our experiment.…”
Section: Discussionmentioning
confidence: 98%
“…This, in turn, promotes the metabolic rate in the magnum, increases the activity of the shell gland, and produces eggshells with enhanced integrity, reducing the loss of carbon dioxide and improving albumen quality. In another study, threonine improved albumen percentage in a dose-dependent manner via upregulation of genes related to AA transport and protein deposition (183). In another study, (34), suggested that supplementing diets that enhance upregulation of AA transporters would enhance albumen synthesis and quality.…”
Section: Amino Acid and Dietary Protein Level Or Sourcesmentioning
confidence: 97%
“…Similarly, lysine supplementation enhanced albumen percentage (182). Also, dietary threonine supplemented in a dosedependent manner increased albumen weight and percentage (183). Improved albumen indices with AA supplementation may be due to increased nutrient concentration and protein levels in the diet (184), which enhance protein synthesis (185).…”
Section: Amino Acid and Dietary Protein Level Or Sourcesmentioning
confidence: 99%
“…The NF-κB signalling pathway plays a key role in inflammation and is involved in the regulation of anti-and proinflammatory cytokines [25]. Proinflammatory cytokines contribute to the host's prevention mechanism of bacterial colonization or invasion [26,27], and anti-inflammatory cytokines inhibit the overactivation of the immune response [28].…”
Section: Introductionmentioning
confidence: 99%